THE EFFICACY AND SAFETY OF DAPAGLIFLOZIN AND SITAGLIPTIN IN PATIENTS WITH UNCONTROLLED TYPE 2 DIABETES: A QUASI EXPERIMENTAL STUDY - IFTIKHAR , F; RAFIQUE , Z; ASGHAR , Z; NIAZI , AW; IFTIKHAR , M; MEHBOOB , M (Biological and Clinical Sciences Research Journal, 2024)
Type 2 diabetes mellitus (T2DM) is a prevalent metabolic disorder that requires effective glycemic control to prevent complications. Dapagliflozin, a sodium-glucose cotransporter-2 (SGLT2) inhibitor, and Sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, are commonly used in combination with Metformin for patients with uncontrolled T2DM. However, there is limited comparative data on the efficacy and safety of these two therapeutic regimens Objectives: To compare the efficacy and safety of Dapagliflozin and Sitagliptin in patients with uncontrolled type 2 diabetes. Methods: After approval from the ethical committee of Islamabad Medical Complex, 250 patients meeting the selection criteria were enrolled. Written informed consent was obtained from patients or their guardians. The patients were divided into two groups: Group A received Dapagliflozin with Metformin, while Group B received Sitagliptin with Metformin. Baseline lab tests were performed and repeated after 12 weeks, along with safety and tolerability assessments. Changes in HbA1c and other parameters were recorded. Efficacy was measured by changes in HbA1c, and safety was evaluated based on reported side effects. Data were collected using a predesigned questionnaire. Results: The study population had a mean age of 45.32 years and a mean BMI of 26.02; 54% were male and 46% female. Most participants (62.4%) were aged 31-50, and 33.2% were over 50. BMI distribution showed 45.6% were of normal weight, while 27.6% were obese. Group A's HbA1c dropped from 9.51 to 7.30 (mean difference: 2.20), and Group B's from 9.39 to 8.16 (mean difference: 1.23), both with p=0.00. Adverse effects included more UTIs in Group A (40.8% vs. 14.4%) and more diarrhea in Group B (38.4% vs. 4.8%), with small differences in other symptoms. Conclusion: The study concluded that both dapagliflozin and sitagliptin effectively reduce HbA1c in uncontrolled type 2 diabetes. Dapagliflozin showed a greater HbA1c reduction but had a higher rate of urinary tract infections, while sitagliptin had fewer UTIs but more gastrointestinal side effects. Further studies are needed to confirm these results and assess long-term safety and efficacy.